Effects of Seclusion and Restraint in Adult Psychiatry: A Systematic Review - Chieze, Marie; Hurst, Samia; Kaiser, Stefan; Sentissi, Othman (Frontiers in Psychiatry, 2019)
Background Determining the clinical effects of coercion is a difficult challenge, raising ethical, legal and methodological questions. Despite limited scientific evidence on effectiveness, coercive measures are frequently used, especially in psychiatry. This systematic review aims to search for effects of seclusion and restraint on psychiatric inpatients with wider inclusion of outcomes and study designs than former reviews. Methods A systematic search was conducted following PRISMA guidelines, primarily through Pubmed, Embase, CENTRAL. Interventional and prospective observational studies on effects of seclusion and restraint on psychiatric inpatients were included. Main search keywords were restraint, seclusion, psychiatry, effect, harm, efficiency, efficacy, effectiveness, quality of life. Results Thirty-five articles were included, out of 6854 records. Studies on the effects of seclusion and restraint in adult psychiatry comprise a wide range of outcomes and designs. The identified literature provides some evidence that seclusion and restraint have deleterious physical or psychological consequences. Estimation of Post-traumatic Stress Disorder incidence after intervention varies from 25 to 47%, and thus, is not negligible, especially for patients with past traumatic experiences. Subjective perception has high interindividual variability, mostly associated with negative emotions. Effectiveness and adverse effects of seclusion and restraint seem to be similar. Compared to other coercive measures (notably forced medication), seclusion seems to be better accepted, while restraint seems to be less tolerated, possibly because of the perception of seclusion as “non-invasive”. Therapeutic interaction appears to have a positive influence on coercion perception. Conclusion Heterogeneity of the included studies limited drawing clear conclusions, but the main results identified show negative effects of seclusion and restraint. These interventions should be used with caution and as a last resort. Patients’ preferences should be taken into account when deciding to apply these measures. The therapeutic relationship could be a focus for improvement of effects and subjective perception of coercion. In terms of methodology, studying coercive measures remains difficult, but in the context of current research on coercion reduction, is needed to provide workable baseline data and potential targets for interventions. Well-conducted prospective cohort studies could be more feasible than RCTs for interventional studies.